A narrativa autobiográfica no 8º ano do Ensino Fundamental: entre a escola e as práticas socioculturais em uma comunidade ribeirinho-quilombola - OLIVEIRA, Ecilia Braga de (Universidade Federal do Pará, 2022)
The purpose of this research is to analyze textual production in Elementary School from autobiographical narratives in a school located in a “ribeirinho-quilombola” community, starting with the sociocultural practices that involve the 8th grade students. The route is intended to work the identity of the learner as transformation agents of themselves and the world that surrounds them, starting from the reality experienced by them to the broader knowledge that dialogues with other realities. The beginning didactic experience, data generation and diagnosis happened between april and december 2019. Based on the grounding and foundation of the study, authors such as Bakhtin (1997, 2012, 2016), Menegassi (2010, 2016), Lopes-Rossi (2005;2008), among others who discuss and analyze the work with the text in the classroom, as well as Thiollent (2011) and Angrosino (2009), who recognize ethnographic research as a methodology that allows us to know the subjects and their worlds. The intervention proposal comprehend reading, writing and linguistic analysis practices in the classroom. It has the goal of arouse new discussions, contributing to a greater attention to the text production in schools, especially in the country school, since it became considerable the need for methodological innovations in classes destined to textual production in communities that are still systematically appropriating the written modality of the language. However, recognize the triad orality, reading and writing for the best performance in the classes of textual production, since more attention will be paid to written and oral production – which obviously does not rule out the importance of reading as the main relevant factor in the absorption of knowledge and dialogues that awaken the relationship between theory and practice, between what is being said and what is actually experienced in sociocultural practices. It is expected to contribute to the development and improvement of a better performance and the role of the student as a textual producer, whether oral or written. For the development of the research, it was choose for the methodological tessitura of action research, a line of research, whose function is to solve problems with a view to the transformation of a reality. The theoretical contribution is bakhtinian sociodiscursive interactionism that talk about the verbal interaction and aspects that cooperate to construct the meanings of the text. The data analysis was performed from the applied questionnaire and from the initial text that allow to understand how the students' writings are. It was not possible to reach analytical results, because of the suspension of classes due to the pandemic of Covid 19. However, the non-application of the intervention proposal redirected the research to be elaborated the educational product "Gamebook Guardians of Açaí", pedagogical material that works the writing through a product whose format is appbook, a book-application, digital and interactive. The pedagogical object dialogued with the sociocultural practices of the countryside subjects to the extent that the narrative is a collective writing that talk about the knowledge of açaí collectors, one of the main economic activities of the region. It was possible to use digital resources (google Meet, WhatsApp) to mediate the written production in the year 2020; This way, think about the factors that contribute to the development of pedagogical practices that stimulate the process of teaching and learning writing in Portuguese by “ribeirinho-quilombolas” students.